2015
DOI: 10.1007/s11745-015-4024-x
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil and Olive Oil Supplementation in Late Pregnancy and Lactation Differentially Affect Oxidative Stress and Inflammation in Sows and Piglets

Abstract: This study was conducted to compare the effects of fish oil and olive oil supplementation in late pregnancy and during lactation on oxidative stress and inflammation in sows and their piglets. A total of 24 sows were fed a basal diet supplemented with additional corn starch (CON), fish oil (FO) or olive oil (OO). Sows fed an OO diet during late gestation had a higher piglet birth weight compared with CON-fed and FO-fed sows (P < 0.05). Furthermore, sows from the OO group had a higher milk fat content than sows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
1
40
1
Order By: Relevance
“…Moreover, a dietary pattern high in red meat has been negatively associated with second‐ and third‐trimester fetal growth parameters. Recent animal data have also shown that maternal olive oil increased piglet birth weight, while reducing plasma interleukin‐1β and tumor necrosis factor‐α levels in the offspring. We suggest that the lower intake of saturated fats and the increased omega‐3/omega‐6 fatty acid ratio, both expected in case of strong adherence to the high fish and olive oil, low meat dietary pattern, could impact on embryonic growth, possibly by modulating inflammation and oxidative stress pathways.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, a dietary pattern high in red meat has been negatively associated with second‐ and third‐trimester fetal growth parameters. Recent animal data have also shown that maternal olive oil increased piglet birth weight, while reducing plasma interleukin‐1β and tumor necrosis factor‐α levels in the offspring. We suggest that the lower intake of saturated fats and the increased omega‐3/omega‐6 fatty acid ratio, both expected in case of strong adherence to the high fish and olive oil, low meat dietary pattern, could impact on embryonic growth, possibly by modulating inflammation and oxidative stress pathways.…”
Section: Discussionmentioning
confidence: 69%
“…All data were checked for normal distribution and homogeneity of variance using the Shapiro-Wilk normality test and Bartlett test, respectively (Shen et al 2015). All data were checked for normal distribution and homogeneity of variance using the Shapiro-Wilk normality test and Bartlett test, respectively (Shen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An individual sow or piglet served as the experimental unit. All data were checked for normal distribution and homogeneity of variance using the Shapiro-Wilk normality test and Bartlett test, respectively (Shen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The serum MDA concentration was measured by reaction with thiobarbituric acid at 95°C and expressed as nmol/ml as previously described by Shen et al. (). The serum T‐AOC was assayed by the reduction in Fe 3+ ‐tripyridyltriazine to Fe 2+ ‐ tripyridyltriazine and expressed as U/ml according to the method of Hu et al.…”
Section: Methodsmentioning
confidence: 99%